Positional differences in professional rugby league match play through the use of global positioning systems - Austin, D. J.; Kelly, S. J. (The Journal of Strength and Conditioning Research, 2013)
The current use of tracking technology in the form of global positioning systems allows for a greater analysis of locomotor activities occurring in games and a larger volume of games when compared with time-motion analysis. Therefore, the aim of this study is to be the first to analyze the physiological demands of forwards and backs throughout the entirety of an Australian professional rugby league season. The movement patterns of 185 players from a professional rugby league club were recorded during 28 National Rugby League games played in Australia during the 2010 season. The players were clustered into 2 positional groups, backs and forwards. Maximum match-play time recorded was 99 minutes and 50 seconds in a semifinal game recorded for both a forward and back. The mean total distances covered in a game for forwards and backs were 5,964 ± 696 and 7,628 ± 744 m, respectively (p < 0.05). The maximum distance recorded by a forward was 10,511 and 10,359 m for a back. The average number of occurrences in high-intensity running (>18 km/h) was 23 ± 4 and for forwards and significantly higher backs with 35 ± 8 (p < 0.05). The maximum work rate in a 10-minute block of match play was 115 and 120 m/min of play for forwards and backs, respectively. Understanding the physiological demands of a sport is important for coaches to deliver athletes optimal training programs that elicit appropriate and specific physiological adaptation. The differences in locomotor activities, which occur between positions, need to be accounted for when developing training programs.